1997
DOI: 10.1017/s0033291797005229
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in male schizophrenics reflect fronto-temporal dissociation

Abstract: These results support the existence of a relative 'fronto-temporal dissociation' in schizophrenia which we suggest may be due to lack of mutually trophic influences during frontal and temporal lobe development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 28 publications
7
50
1
1
Order By: Relevance
“…However, the associations we detected may be disrupted in some patient populations, although the mean regional densities per se may not be affected. In the only example of this sort, Woodruff et al (1997) demonstrated a dissociation between gray matter volumes of superior temporal and frontal cortex in schizophrenics relative to controls, although neither region individually differed in mean volume between the two groups. The approach we use here may therefore be useful to investigate patterns of associations in patients and controls or in different groups of patients.…”
Section: Discussionmentioning
confidence: 94%
“…However, the associations we detected may be disrupted in some patient populations, although the mean regional densities per se may not be affected. In the only example of this sort, Woodruff et al (1997) demonstrated a dissociation between gray matter volumes of superior temporal and frontal cortex in schizophrenics relative to controls, although neither region individually differed in mean volume between the two groups. The approach we use here may therefore be useful to investigate patterns of associations in patients and controls or in different groups of patients.…”
Section: Discussionmentioning
confidence: 94%
“…However, in our review of 49 MRI studies, we note a large number of studies that demonstrate left-lateralized findings for the amygdala-hippocampal complex, particularly in male patients (e.g. Barta et al, 1990Barta et al, , 1997aBogerts et al, 1990Bogerts et al, , 1993bBreier et al, 1992;DeLisi et al, 1988;Hirayasu et al, 1998;Kawasaki et al, 1993-parahippocampal gyrus only;McNeil et al, 2000;Ohnuma et al, 1997;Razi et al, 1999;Rossi et al, 1994a;Shenton et al, 1992;Stefanis et al, 1999;Velakoulis et al, 1999;Woodruff et al, 1997b).…”
Section: Temporal Lobe Findingsmentioning
confidence: 86%
“…248 Some studies were only able to find evidence for significantly smaller left hippocampal volume. [255][256][257] Stefanis et al 258 found evidence for smaller left hippocampi only in patients with schizophrenia and birth complications. Others have failed to find any evidence of smaller hippocampi in patients with schizophrenia, compared to controls.…”
Section: Schizophreniamentioning
confidence: 99%